A narrativa corporificada na dança: um caminho para a resiliência e a ressignificação do indivíduo - Luna, Sávio Jordan Azevedo de (2018)
This research has as base and works the context between autobiographical narrative writing and dance, aiming to take a way to the inter-relation and synergy between self-resilience and self-resignation. It consists in a symbiotic affinity between writing and dance, through an intimate relationship that writes, produces, resigns, changes, reframes, creating new perceptions, new reflections, new experiences, that brings to the person a new consciousness and condition. This investigation points to, during writing and dance creation, two states of perception and simultaneous and consequence production. The first one shows a direct and at the distance self-narrative writing that aim to understand experience; the last one shows desire and necessity of the production of resilience, of becoming free from undesired ties that came from the past, through dance creation, when imagination and the act to express creatively emerge and become the way to human emancipation. To this, it realizes interview with four interpreters/dance creators, then each one had a chance to tell their experiences and reasons to practice dance, and its transforming effects in their lives and, consequently, the emergence of creation. The questionnaire, applied orally, had semi opened questions from exploratory-descriptive nature, and after the transcription of the testimonies. In addition to this, it had a part of writing narratives. Based on this corpus, it analyzed, at the end of narratives, an autobiographical narrative writing that pushes interviewers to the resilient process and, therefore, to self-reframing in a psychological and social context, respectively. The methodology used strategically a case of study, based on an interpreter-creator dancer group from Espaço Cultural Gira Dança in Natal-RN, with a qualitative approach, analyzing different and resilient histories and experiences that there are in the book Autobiografia de um Espantalho (CYRULNIK, 2009), as reference and theoretical support. This research aims to show symbioses in the state of resilience that came from autobiographic oral and writing testimonies related to dance experience and creative production that take dancers to changes by the reframing process. This research, therefore, links, reflects, and points to the inter-section and synergies between arts, that came from writing narratives or from dance, and the individual resilience. It points resilient creative power that can, consequently, overcome trauma, showing the way to a more generous, human, and welcoming world, that promotes self-reframing and situates person in her/himself, related to other people, and to the world around, bringing new senses and new perceptions linking the past and memory, with this, the boundaries between narrative, writing and dance together take this person, without mishaps and fences, to the total and free divagation, according to Gaston Bachelard (1988, 1990, 2009).